Private hajj package: agency management at Tabung Haji - Abd Rahman, Azmawani; Hussin, Siti Rahayu; Abdul Latiff, Ahmed Razman (Universiti Putra Malaysia Press, 2014)
This case discusses the management of private hajj package at TH. It gives readers greater insight on the connection between TH and the appointed agencies and on issues related to hajj operations. The purpose of this case is to expose reader to the concept of effective principle agent relationship management for superior customer satisfaction and business performance. The main part of the case illustrates the effort taken by TH to ensure the service quality of the appointed agencies as the pengelola jemaah haji (PjH). Issues that posed challenge to the agencies and its management such as on quota reduction and on the presence of fake hajj package are also discussed. The case provides the opportunity for readers to discuss the expected benefits from superior agency management and relate that to TH experience. In addition, this case enables readers to evaluate the challenges from various perspectives such as through the external environment framework or through the project management aspect.